Odpowiedź:
a) A + B= 5x + y = 5 · 1 + (-1) = 5 - 1 = 4
b) A - B = x - 5y = 1 - 5 · (-1) = 1 + 5 = 6
c) B - A = -x + 6y = -1 + 6 · (-1) = -1 - 6 = -7
Szczegółowe wyjaśnienie:
A = 3x – 2y, B = 2x + 3y
Doprowadź podane wyrażenie do najprostszej postaci i oblicz jego wartość dla
x = 1 i y = -1
a) A + B= 3x - 2y + 2x + 3y = 5x + y = 5 · 1 + (-1) = 5 - 1 = 4
b) A - B = 3x - 2y - (2x + 3y) = 3x - 2y -2x - 3y = x - 5y = 1 - 5 · (-1) = 1 + 5 = 6
c) B - A =2x + 3y - (3x - y) = 2x + 3y - 3x + 3y = -x + 6y = -1 + 6 · (-1) = -1 - 6 = -7